Peningkatan Kemampuan Pemecahan Masalah Pada Materi Sistem Persamaan Linear Dua Variabel Melalui Aplikasi Pembelajaran Blended Learning Berbasis Edmodo - Faisal; Raudatul Husna; Sarah Yulis (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This study aims to determine the effect of the Blended Learning learning model based on the Edmodo application on the mathematical problem solving ability of students in class VIII of SMPN 2 Indrajaya, Pidie Regency. The research method used is quasi-experimental using a pretest-posttest research design. The population of this study were all eighth grade students of SMP Negeri 2 Indrajaya, Pidie Regency. The samples used in this study were two classes, namely class VIII.2 which amounted to 30 students and class VIII.3 which amounted to 27 students. The data collection technique used is a test sheet in the form of an essay to measure students' mathematical problem solving abilities. The hypothesis test uses a one-sided T-test, namely the right-hand T-test. The results showed that the average mathematical problem solving ability of students in the experimental class was 28.1583 while the average mathematical problem solving ability of students in the control class was 21.6690. After the average difference test was carried out, it was obtained that tcount ≥ t table 7,56≥1,67 so that Ha was accepted, which means that the mathematical problem solving ability of students who were taught with the Edmodo application-based Blended Learning learning model was better than students who studied with the conventional model.